Swiss Democracy Possible Solutions to Conflict in Multicultural Societies - Linder, Wolf (Springer Nature, 2021)
This open access book provides an updated and fully revised 4th edition of this authoritative analysis of Swiss democracy. It particularly explains the institutions of federalism and consensus government through political power sharing. In this new edition, the authors also address several important changes and challenges that have affected Swiss democracy, including the country's relationship with the EU, fiscal equalisation, direct democracy and the legitimacy of national referendums, territorial conflict, as well as the polarisation of party politics.